Соборність – ключова ідея у редакційній політиці газети «Буковина» (1895-1897 рр.) - Попович, Юлія Олександрівна (Ingvarr, Lublin, Poland, 2016)
The article is devoted to media coverage of the idea of unity on the pages of the Chernivtsi magazine “Bukovyna” in 1895 – 1897. During this period the newspaper reached the highest rise in its development due to the editorial talent of Osyp Makovey. He continued to embody the strategic program of the newspaper aimed at the awakening of national consciousness of Ukrainians and their spiritual unity around the idea of build ing their own state.
UNITY AS A KEY IDEA IN THE EDITORIAL POLICY OF THE NEWSPAPER "BUCOVYNA" (IN 1895-1897)
Keywords: magazine, newspaper, national idea, unity, content, history of the press; журнал, газета, національна ідея, соборність, історія преси